Online learning of socio-emotional behaviors in primary education during the COVID 19 pandemic. Case study - Manta, Oana Corina; Enache, Rodica Gabriela (Technium Social Sciences Journal, 2021)
In this paper we will analyze the characteristics of socio-emotional behaviors of primary school students in online learning conditions, the psycho-educational needs of students and socio-emotional learning, as well as a number of educational intervention strategies (positive teaching, positive discipline, assertive discipline).